A Review on Comparison of Face Recognition Algorithm Based on Their Accuracy Rate - Ravat, Rashmi; Dhanda, Namrata (International Journal of Computer Sciences and Engineering, 2015)
This paper tries to present an overview of different face recognition techniques and study the characteristics of various algorithms developed for “feature selection” and “feature extraction”. Study and analysis of the face recognition rate of various face recognition algorithms, used currently, is imperative for designing and developing a new Algorithm. In his paper we report performance comparison analysis of Principal Component Analysis (PCA), Linear Discriminant Analysis (LDA), ICA, SVM & SVD for face recognition. Various PCA and LD, ICA; SVM & SVD based face recognition algorithms were studied and compared in this paper. Standard public database was utilized for this purpose.